A NEED TO CREATE A SOCIETY OF PROFESSIONAL ARCHAEOLOGISTS IN THE PHILIPPINES - Jago-on, Sheldon Clyde B. B. (Hukay; Vol 1 No 2)
This paper lays out the reasons why the creation of a Society of Professional Archaeologists in the Philippines is an immediate concern. Much of the Philippine archaeological sites have been desecrated and/or lay unprotected, making them easy preys for treasure and pot hunters. Only a professional society then can focus on the institutionalization of the discipline with the aid of other government and nongovernment agencies concerned with the preservation of Philippine Cultural Heritage. The qualification requirements to be a member include both academic and field experience. A minimum number of academic units and weeks of field experience in archaeological exploration and/or excavation are set. The society is primarily geared towards protecting Philippine archaeological sites, conducting archaeological activities in the field, and publishing archaeological field and laboratory reports.